The impacts of coastal erosion on Alaska's North Slope communities: a co-production assessment of land use damages and risks. (1st October 2020) - Brady, Michael B.; Leichenko, Robin
ABSTRACT: The impacts of coastal erosion on municipal infrastructure and property have been widely documented within coastal Alaska. Less is known, however, about erosion-related impacts on natural resource-based land uses that contribute to the well-being of Alaska's Native residents. This study explores erosion impacts on resource-based land uses on Alaska's North Slope. The study utilized a collaborative mapping workshop approach, in which research participants defined major categories of land use impacts, identified locations most at risk, and described key local and regional effects of erosion. The study findings highlight three critical types of land use impacts associated with coastal erosion. These include: (1) disruption of subsistence hunting; (2) losses associated with damaged military radar assets (DEW-Line); and, (3) constrained hydrocarbon related development opportunities on land controlled by Native corporations. Through specification of locally relevant land use impacts, the study findings contribute to a better understanding of how climate change is undermining cryosphere-related ecosystem services, particularly buffering cultural and economic activity from coastal storms. The study results reinforce the utility and value of co-production approaches for Arctic climate impact assessments. Through integration of local perspectives on erosion risks, the study contributes to collective regional knowledge about climate change risks to Arctic communities.